Microsurgical Clipping after Failed Contour Device Embolization of an Anterior Communicating Artery Aneurysm: Technical Note - Griessenauer, Christoph J.; Killer-Oberpfalzer, Monika; Beredjiklian, Carlos M.; Lunzer, Manuel (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2023)
Background Endovascular therapy has revolutionized the treatment of cerebral aneurysms in recent years and decades. So-called intrasaccular devices (i.e., Woven EndoBridge [WEB], MicroVention, Aliso Viejo, California, United States; or Contour, Cerus Neurovascular, Fremont, California, United States) are a promising endovascular technology, especially for wide-based aneurysms. However, long-term outcome data are currently particularly scarce for Contour and strategies for failed Contour cases are lacking. Here, we report the feasibility of microsurgical clipping after failed Contour device embolization.Methods Feasibility of microsurgical clipping after failed aneurysm embolization with a Contour intrasaccular device was assessed in a patient.Results We present the case of a 36-year-old male patient diagnosed with Hunt and Hess grade 1 subarachnoid hemorrhage from an anterior communicating artery aneurysm. The ruptured aneurysm was initially treated with the Contour device. After 3 months, angiographic imaging showed a clear aneurysm residual deemed not endovascularly accessible. The patient was then successfully clipped using microsurgical techniques. The patient was discharged with no neurologic abnormalities.Conclusion After thorough bibliographical research, this presents the first published case report of microsurgical clipping after failed embolization with Contour. The main insights gained after clipping were that the Contour does not significantly disturb or hinder clipping. In contrast to coils in aneurysms to be clipped, the Contour can be easily compressed by the clip blades and does not have to be removed. In addition, the Contour had not migrated into the subarachnoid space and there was no abnormal scarring. Clipping appears to be a reasonable treatment strategy for failure of embolization with Contour if endovascular means are not suitable.
Keywords: aneurysm; cerebral; clipping; endovascular; intrasaccular; embolization